Nilai CT RdRp Polymerase Chain Reaction Sebagai Faktor Prediktor Mortalitas Pasien COVID-19 - Choirunisa, Anjani Feby; Rahayu, Rahayu; Istiqomah, Istiqomah (Jurnal Penelitian Kesehatan SUARA FORIKES, 2024)
COVID-19 is an infectious disease caused by the SARS-CoV-2 virus. The Ct (cycle threshold) value correlates with the amount of virus in the body. A high viral load is proportional to a low Ct value. An increase in viral load has an impact on increasing mortality. This study aimed to determine the Ct value as a predictor of mortality in COVID-19 patients. This study was an analytical observational study with a cross-sectional design on inpatients diagnosed with COVID-19 in 2021. The inclusion criteria in this study were patients aged 18-60 years, with moderate or severe clinical symptoms. Exclusion criteria were patients with autoimmune diseases, HIV/AIDS, history of malignancy, history of radiotherapy and/or chemotherapy. The patient's Ct RdRp value and mortality status were checked, and then a binary logistic regression test was carried out. The research results showed that of the 70 COVID-19 patients, 35 (50%) recovered and 35 (50%) died. The percentage of mortality in patients with low and high Ct values was 68.6% and 31.4%, respectively. The results of the binary logistic regression test on the effect of Ct value on mortality showed a p value of less than 0.001 and the Odd ratio was 13.09. The conclusion of this study was that low Ct values can be determined as a predictor of mortality in COVID-19 patients.Keywords: predictor factors; mortality; Ct value; RT-PCR; viral load  ABSTRAK COVID-19 merupakan penyakit menular yang disebabkan oleh virus SARS-CoV-2. Nilai Ct (cycle tresshold) berkorelasi dengan jumlah virus dalam tubuh. Viral load tinggi sebanding dengan nilai Ct yang rendah. Peningkatan Viral load memberikan dampak terhada peningkatan mortalitas. Penelitian ini bertujuan untuk mengetahui nilai Ct sebagai faktor prediktor mortalitas pasien COVID-19. Penelitian ini merupakan penelitian observasional analitik dengan desain cross-sectional pada pasien rawat inap dengan diagnosis COVID-19 pada tahun 2021. Kriteria inklusi dalam penelitian ini adalah pasien usia 18-60 tahun, dengan gejala klinis sedang atau berat. Kriteria eksklusi adalah pasien dengan penyakit autoimun, HIV/AIDS, riwayat keganasan, riwayat radioterapi dan/atau kemoterapi. Pada pasien dicek nilai Ct RdRp dan status mortalitas, dan selanjutnya dilakukan uji regresi logistik biner. Hasil penelitian menunjukkan bahwa dari 70 pasien COVID-19, sebanyak 35 (50%) sembuh dan 35 (50%) meninggal. Persentase mortalitas pada pasien dengan nilai Ct rendah dan tinggi masing masing sebanyak 68,6% dan 31,4%. Hasil uji regresi logistik biner tentang pengaruh nilai Ct terhadap mortalitas menunjukkan nilai p kurang dari 0,001 dan Odd ratio adalah 13,09. Kesimpulan dari penelitian ini adalah bahwa nilai Ct yang rendah dapat ditentukan sebagai faktor prediktor mortalitas pasien COVID-19.Kata kunci: faktor prediktor; mortalitas; nilai Ct; RT-PCR; viral load